1994
DOI: 10.3354/dao018217
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in hemocytes and serum defense factors in the blue mussel Mytilus galloprovincialis

Abstract: Hemolymph characteristics were examined in experimentally cultured blue mussels Mytilus galloprovincialis Lmk, from 2 locations in the Ria d e Vigo (NW Spain). The highest protein, lysozyrne and agglutinin values were found in July. The increase of agranular hemocytes and the decrease of granular blood cells in April was associated with parasitism by Mytilicola intestinalis. No linkage was found between the number of circulating hemocytes and hemolymph component (lysozyrne, agglutinins and proteins) concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 20 publications
1
33
1
Order By: Relevance
“…This variation may reflect the biological characteristics of the individuals, their physiological state and the environmental conditions (Auffret & Oubella 1995), and may be related to the haemopoietic activity of the bivalves (Anderson 1990, Pipe et al 1995. The number of haemocytes were influenced by seasonal factors (such as temperature, reproductive cycle, food), as reported by Santarèm et al (1994) for Mytilus galloprovincialis. Feng (1965) reported that the number of circulating haemocytes in Crassostrea virginica is influenced by the amount of food and the temperature.…”
Section: Discussionmentioning
confidence: 94%
“…This variation may reflect the biological characteristics of the individuals, their physiological state and the environmental conditions (Auffret & Oubella 1995), and may be related to the haemopoietic activity of the bivalves (Anderson 1990, Pipe et al 1995. The number of haemocytes were influenced by seasonal factors (such as temperature, reproductive cycle, food), as reported by Santarèm et al (1994) for Mytilus galloprovincialis. Feng (1965) reported that the number of circulating haemocytes in Crassostrea virginica is influenced by the amount of food and the temperature.…”
Section: Discussionmentioning
confidence: 94%
“…A possible linking factor between these latter elements could be the reproductive cycle, which can affect haemocytes and which is also a means by which molluscs can remove hydrocarbons. A field study in Spain on Mytilus galloprovincialis recorded strong seasonal effects on haemocyte numbers, which were attributed principally to reproductive effects (Santarém et al 1994). Alternatively, factors such as salinity or temperature can influence bivalve immunity (Fisher & Newall 1986, Chu & LaPeyre 1993, although they may have less direct roles than the reproductive cycle in hydrocarbon accumulation/depuration.…”
Section: Discussionmentioning
confidence: 99%
“…Lysozyme activity was quantified according to Santarem et al (1994). CL (50 µl), obtained as described above, was added to 950 µl of a 0.15% suspension of Micrococcus lysodeikticus (Sigma) in 66 mM phosphate buffer, pH 6.2, and the decrease in absorbance (∆A min -1 ) was continuously recorded at 450 nm for 5 min at 20°C.…”
Section: Animalsmentioning
confidence: 99%